Improve stability of high order sigma-delta modulators - Uçar, A (Inst Electrical Engineers Inspec Inc, 1999)
In this paper, a compensation technique is given for high order sigma-delta modulator to improve their stability and prevent the clipping effect.
3rd International Conference on Advanced A/D and D/A Conversion Techniques and their Applications -- JUL 27-28, 1999 -- UNIV STRATHCLYDE, GLASGOW, SCOTLAND
Keywords: Quantization Noise